Artificial Intelligence dan Literasi Digital Pelaku UMKM: Tantangan Dan Peluang dalam Transformasi Bisnis - Arjang; Endang Sri Wahyuningsih; Hizbul Khootimah Azzaakiyyah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Advances in Artificial Intelligence (AI) are driving significant changes in business practices, including within the Micro, Small and Medium Enterprises (MSME) sector, which is required to adapt to the dynamics of the digital economy. This study aims to analyse the role of digital literacy in supporting the adoption of AI and to identify the challenges and opportunities faced by MSME operators in the business transformation process. The method employed is a literature review using a qualitative approach and descriptive analysis of 39 selected articles from a total of 50 initial sources obtained via Google Scholar and various credible websites spanning the years 1984–2026. Data analysis was conducted through the stages of data reduction, data presentation, and drawing descriptive conclusions. The results of the study indicate that digital literacy has a strong influence on the ability of SME operators to understand and utilise AI technology, which impacts improvements in operational efficiency, service quality, and business performance. The findings of this research confirm that the success of SME digital transformation is largely determined by the readiness of human resources and adequate ecosystem support. The limitations of this study lie in the use of secondary data and a qualitative approach, meaning that the results of the analysis do not yet measure the specific relationships between variables. Further research is recommended to employ quantitative or mixed-methods approaches using primary data, so that the results are more contextual and measurable.